Behind the eco-friendliness of “batik warna alam”; Discovering the motives behind the production of batik in Jarum village, Klaten - Handayani, Widhi; Kristijanto, Augustinus Ign; Hunga, Arianti Ina Restiani (Wacana, Journal of the Humanities of Indonesia, 2018)
The policy of sustainable production has encouraged small batik businesses to shift to natural dyes as these are considered eco-friendly. However, the motivation behind juragan batiks’ embracing natural dyes still has some question marks attached. This qualitative study explains the motivation of the juragan batiks in using natural colourants in their production of batik warna alam and explores the significance of batik warna alam to juragan batik. We found the production of batik warna alam tended to be triggered by economic reasons not environmental consciousness. This related to the meaning of batik warna alam to maintaining the economic survival of the juragans. Juragans are convinced that batik warna alam is eco-friendly according to the indicators to which they subscribe: (1) the materials are found in their immediate surroundings; (2) the process causes no pollution or environmental destruction; and (3) the production does not pose a health threat to people, including workers. This study provides the insight that an eco-friendly-labelled production might not necessarily be motivated by a high level of environmental consciousness.